Moisture Accumulation and Durability of Panel Walls in Aggressive Environment (Eurasian Journal of Engineering and Technology, 2022)
The article studies the kinetics of moisture accumulation of saline enclosing structures and studies the effect of volumetric hydrophilization on the salinization process and durability of enclosing structures.